Sesame and Lilies - Ruskin, John, 1819-1900 (Salt Lake City, UT : Project Gutenberg, 1998)
"Sesame and Lilies" by John Ruskin is a philosophical and literary work composed in the mid-19th century. The book is structured as a series of lectures that addresses topics related to education, the value of literature, and the moral responsibilities of individuals, particularly focusing on women and their roles in society. It serves as a critique of contemporary cultural and educational standards, urging readers to pursue valuable knowledge and leading a life of purpose. At the start of the text, Ruskin introduces the core themes of the first lecture, "Sesame," wherein he reflects on the importance of figurative kings' treasuries as a metaphor for the treasures found in books. He stresses that reading should not only be about gaining knowledge but also about seeking truths and fostering moral character. He critiques society's focus on social status and material advancement, urging the necessity of possessing and cultivating a meaningful library filled with beneficial literature. The opening reveals Ruskin's intention to encourage young readers, particularly women, to seek a purposeful, thoughtful existence while promoting ideas of self-improvement and social responsibility. (This is an automatically generated summary.)
Release date is 1998-04-01
Transcribed from the 1894 George Allen edition by David Price
Keywords: Conduct of life; Social problems; Women; Books and reading -- Great Britain